Analisis Hubungan Keterampilan Berpikir Kritis dengan Kecenderungan Berpikir Kritis Mahasiswa Calon Guru Sekolah Dasar - Hasnawati Hasnawati; Baiq Niswatul Khair; Itsna Oktavianti (Jurnal Syntax Transformation, 2021)
Critical thinking competence is one of the demands of education in this century, so analyzing the extent to which the critical thinking abilities of candidate teachers is important for LPTKs as a reference for providing appropriate programs for the birth of teachers who have good critical thinking skills. This study aims to analyze the relationship between Critical Thinking Skills and Critical Thinking Dispositions of elementary school teacher candidate. The method used in this research is quantitative and qualitative methods. The sample was 91 people who were selected by purposive sampling and were students of the Mataram University Elementary School Teacher Education Study Program. Data on critical thinking dispositions were obtained through the CCTDI questionnaire and data on critical thinking skills were obtained through multiple choice three tier tests. The results of data analysis obtained 42.86% level of critical thinking skills of prospective elementary school teacher candidate in the high category and 57.14% in the medium category. Meanwhile, critical thinking dispositions is 5.49% in the strong category and 94.51% in the positive category. The results of the correlation test between the two obtained an r value of 0.290 which indicates that there is a significant positive relationship between the critical thinking skills and critical tahinking dispositions. Based on these results, it can be concluded that teacher candidate who have high critical thinking dispositions can also have high critical thinking skills and vice versa